Relapse of Infiltrating Lobular Carcinoma with Distant Metastasis and Malignant Pleural Effusion after 7 Years of Disease-Free Survival: A Case Report - Klein, MD MPH, Jenn; Abraham, MD, Sunoj (International Journal of Innovative Research in Medical Science, 2022)
Breast cancer relapse remains a common cause of morbidity and mortality in patients who initially underwent surgical treatment with or without chemotherapy and radiation. Rates of recurrence are highest in the first two years after diagnosis but the rate of relapse remains persistent more than a decade after diagnosis. Additionally, pleural metastasis of breast cancer, which often presents as a malignant pleural effusion, typically occurs during the first few years after diagnosis but is not common after a long period of disease-free survival. This is a case of breast cancer relapse after 7 years of disease-free survival with lung metastasis and malignant pleural effusion secondary to pleural metastasis and without locoregional recurrence.